Exposure of lead on intestinal structural integrity and the diversity of gut microbiota of common carp - Zhang, Yue; Zhang, Peijun; Shang, Xinchi; Lu, Yuting; Li, Yuehong (Comparative biochemistry and physiology. Toxicology & pharmacology, 2021)
Lead is an environmental toxicant that has toxicity effect to the health of aquatic organisms. Gut microbiota has been reported to be closely related to human health. The aim of this study was to investigate the effects of lead exposure on the composition of gut microbiota. The composition of gut microbiota alteration was detected by 16S rRNA gene sequencing, following a 42-day exposure of lead (1 mg/L). The results showed that compared with the normal control group, the carp of lead group showed severe intestinal tissues injury and decreased Zona Occludens 1 (ZO-1) and occludin expression. The production of LPS in serum was increased by the treatment of lead exposure. Our results showed gut bacterial diversity in lead-treated common carp was lower than the control group. At the phylum level, the abundance of Bacteroidetes (LPS producing bacteria) and Fusobacteria in lead-treated carp were much higher than the control carp. And the abundance of Actinobacteria decreased by lead exposure. At the genus level, we found the abundance of Bacteroides (LPS producing bacteria) and Plesiomonas (an important pathogenic bacteria), increased significantly by lead exposure. And the abundance of Akkermansia, a critical probiotics, was markedly inhibited by lead exposure. In conclusion, this study indicated exposure of carp to lead causes gut microbiota alterations and intestinal structural integrity destruction. [Display omitted] •The carp of lead group showed severe intestinal tissues injury and decreased ZO-1 and occludin expression.•Gut bacterial diversity in lead-treated common carp was lower than the control group.•At the phylum level, the abundance of Bacteroidetes and Fusobacteria increased significantly by lead exposure.•At the genus level, the abundance of Bacteroides and Plesiomonas increased significantly by lead exposure.•And the abundance of Akkermansia was markedly inhibited by lead exposure.